MENINGKATKAN KEGIATAN MENGANYAM UNTUK MENINGKATKAN MOTORIK HALUS ANAK KELOMPOK B DI TK MUTIARA HATI - Hasanah, Qudwatun; Rachmayani, Ika; Nada Buahana, Baiq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the fine motor skills of Group B children at Mutiara Hati Kindergarten through weaving activities. The study employed the Classroom Action Research (CAR) method, conducted over three cycles. The subjects consisted of 10 children from Group B. Data collection was carried out through observation and documentation, while data analysis utilized quantitative descriptive analysis. In Cycle I, the implementation rate of the weaving activity reached 81.25%, while the children's fine motor skills reached 36.66%, falling into the "Beginning to Develop" (MB) category. In Cycle II, the implementation rate rose to 87.5%, and the children's fine motor skills improved to 56%, placing them in the "Developing as Expected" (BSH) category. Finally, in Cycle III, the implementation rate increased to 94% (rated as "Very Good"), and the children's fine motor skills improved to 83.33%, falling into the "Developing Very Well" (BSB) category. Thus, it can be concluded that weaving activities using buffalo paper are effective in improving the fine motor skills of Group B children at Mutiara Hati Kindergarten.